Trufax about discussion group netspeak : an historical analysis of semantic change in the English slang of newsgroups and web forums - Turton, Stephen (My University, 2014)
This dissertation offers an examination of the ways in which English writers in Internet discussion groups—that is, newsgroups and web forums—draw upon techniques of semantic change to create slang words. The dissertation hypothesizes that the techniques involved will be similar to those found underpinning semantic change in other varieties of the English language, both the standard form and other, offline varieties of modern slang. However, the precise constraints of the online platform—its basis in text rather than speech and gesture—will also lead to some differences in how the semantic change is carried out. The hypothesis is put to the test using diachronic analyses of 67 slang words, which are represented in data drawn from a variety of Internet discussion groups dating from 1980 to the present day. In analysing these words, the dissertation also examines whether the techniques documented are explainable within established theoretical frameworks of semantic change, particularly whether they conform to the tendencies in the directionality of semantic change identified by Elizabeth Close Traugott as part of her Invited Inferencing Theory of Semantic Change.